Influence of Nanomaterial Modifiers on Fatigue Resistance of Asphalt Concrete Mixtures: A Review Paper (Journal of Engineering, 2025)
Enhancing fatigue resistance in asphalt binders and mixtures is crucial for prolonging pavement lifespan and improving road performance. Recent advancements in nanotechnology have introduced various nanomaterials such as alumina (NA), carbon nanotubes (CNTs), and silica (NS) as potential asphalt modifiers. These materials possess unique properties that address challenges related to asphalt fatigue. However, their effectiveness depends on proper dispersion and mixing techniques. This review examines the mixing methods used for each nanomaterial to ensure uniform distribution within the asphalt matrix and maximize performance benefits. Recent research findings are synthesized to elucidate how these nanomaterials and their mixing processes enhance mechanical properties, durability, and overall pavement performance. Evidence suggests that incorporating well-dispersed nanomaterials significantly improves fatigue resistance, leading to reduced cracking and extended pavement life. The review concludes that integrating nanotechnology with effective mixing strategies presents a potentially effective approach for advancing asphalt technology, optimizing performance across diverse environmental conditions, and paving the way for more resilient infrastructure.